Using peristomal body profile assessment to improve leakage-related quality of life for individuals with an ostomy. (23rd February 2023) - Vendelbo, Grethe; Carlsson, Eva; Tøndel, Lise Toril; Myller, Elena; Sternhufvud, Catarina; Simonsen, Kenneth Starup; Munch, Philip; Petersen, Birte
Abstract : Background: Improper fitting between peristomal body profile and ostomy product(s) is one of the main reasons for leakage among individuals with an ostomy. Aim: To evaluate clinical usability of the Body Assessment Tool developed by Coloplast that is available free of charge. The aim was also to study how changing to product(s) that were best suited to an individual, guided by peristomal body profile, affected the number of leakages and individuals' quality of life. Methods: The study consisted of questionnaires administered before and after the study, which spanned 4–5 weeks. A total of 22 nurses and 68 individuals with an ostomy participated in four Nordic countries. Findings: Of the 22 nurses, 21 recommended use of the tool. A shift to best fitting ostomy product(s) resulted in a significant decrease in the number of leakages (from 5.9 to 1.8 per 7 days) and a substantial improvement in quality of life. Conclusion: The findings support the use of the Body Assessment Tool in clinical practice and the results showed that optimally fitting ostomy product(s) reduced the number of leakages and increased individuals' quality of life.